SYNTHESIS AND PRINCIPAL PHYSICO-CHEMICAL CHARACTERISTICS OF GALLIUM-GERMANIUM ANALOGS OF ANDALUSITE AND X-ANDALUSITE - Sorokina S.L.; Balitskiy V.S.; Bondarenko G.V.; Gorogotskaya L.I. (My University, 1990)
One of the unsolved problems of experimental mineralogy is the synthesis of single crystals of anadalusite. Because of the geochemical similarity of aluminum to gallium, and of silicon to germanium. This permits the use of the Ga2O3-GeO2 and Ga2O3-GeO2-H2O systems as models for the study of phase development in aluminosilicate systems. In this context we tried to synthesize a gallium-germanium analog these systems. The experiments used both hydrothermal and solid-state methods. Under hydrothermal conditions, phase development in the Ga2O3-GeO2-H2O system were studied with the addition of the mineralizing agents HCl and NH4Cl. The experiments were carried out at temperatures of 250 to 450°C and pressures from 300 to 1000 atmospheres. The initial charge consisted of a mechanical mixture of Ga2O3 (99.95% chemically pure reagent) and GeO2 (specially pure chemical reagent, hexagonal form). Our studies have shown that under hydrothermal conditions in a gallium-germanate system, as in an aluminosilicate, a phase with the structure of x-andalusite is produced, but under lower temperature and pressure conditions: under the conditions indicated, in the Ga2O3-GeO2 system, unlike in the system Al2O3-SiO2 crystals with the structure of andalusite are produced in solid-sate synthesis.